2019
DOI: 10.1007/s13197-019-03718-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a functional food (pan bread) using amla fruit powder

Abstract: The amla fruit powders were analyzed for ascorbic acid, sugars, pectin, total phenolics (TPC), and total antioxidant activities (TEAC). Fresh amla was found to have 6644.305 mg/100 g ascorbic acid with sun-dried, oven-dried and freeze-dried having 748.427 mg/100 g, 641.364 mg/100 g, 791.233 mg/100 g, respectively. There were no significant differences for the TPC values which ranged from 113.1 for oven-dried (OD), 128.7 for sun-dried (SD), 161.2 mg for freeze-dried (FD) and 1410.5 GAE/g for fresh amla pulp (FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 29 publications
(33 reference statements)
2
24
0
Order By: Relevance
“…Thus, higher antioxidant activity of the samples was contributed by the chutney samples with higher TPC. Higher amount of polyphenols, antioxidant and ascorbic acid was reported in amala products [12,28]. Lower acidity and higher pH was reported with the decrease in the amala pulp proportion in the chutney samples (Table 6).…”
Section: Chemical Phytochemical Analysis and Antioxidant Activity Ofmentioning
confidence: 80%
See 1 more Smart Citation
“…Thus, higher antioxidant activity of the samples was contributed by the chutney samples with higher TPC. Higher amount of polyphenols, antioxidant and ascorbic acid was reported in amala products [12,28]. Lower acidity and higher pH was reported with the decrease in the amala pulp proportion in the chutney samples (Table 6).…”
Section: Chemical Phytochemical Analysis and Antioxidant Activity Ofmentioning
confidence: 80%
“…Although amla fruit is one of the richest sources of ascorbic acid (445-468 mg of vitamin C/100 g amala fruit) and has many phenolic compounds, but the sour and astringent taste makes the fresh amala fruit less acceptable to consumers [27]. Total sugar reducing and nonreducing sugars were less than that of findings of Parveen and Khatkar [23] but higher than the findings of Ranote et al [26].Total polyphenol content (TPC) and total flavonoid content (TFC) was found less than the findings of Alkandari et al [28] but higher than the findings of Ruangchakpet and Sajjaanantakul [29]. Tannin content in the amala fruit was found to be 245.49 mg GAE/g.…”
Section: Nutritional and Chemical Composition Of The Fresh Amala Fruitmentioning
confidence: 95%
“…Amla (Phyllanthus emblica L), the Indian Gooseberry is a rich source of ascorbic acid that serves as an oxidizing agent in strengthening the gluten by interfering with the reducing activity of the naturally present tripeptide glutathione in the wheat flour (Schroeder and Hoseney, 1978;Sidhu et al, 1980Sidhu et al, , 2001. In recent publications, Alkandari et al (2019aAlkandari et al ( , 2019b demonstrated an improvement in the specific loaf volume of wheat bread when amla fruit powder was substituted for potassium bromate, which is still commercially being used as a dough improver in bread in some countries. Bread being a low cost, easily available staple food for majority of the world population, has been under extensive research with a challenge to achieve nutritional improvement without compromising sensory attributes.…”
Section: Introductionmentioning
confidence: 99%
“…Fresh amla fruit procured from the local market was dried by three different techniques, fresh amla as well as dried amla powders were analyzed for proximate composition, antioxidant capacity, white flour bread was made with amla powders and then analyzed for proximate composition, TEAC, TPC, baking quality and sensory characteristics, which have been presented in an earlier publication (Alkndari et al 2019). The data related to specific loaf volume and baking loss in bread samples is presented in supplementary Table 1s.…”
Section: Resultsmentioning
confidence: 99%
“…Fresh fruit pulp was also freeze-dried (GAMMA 1-16 LSC, UK) until the moisture content reached lower than 2%. It was then powdered, labeled as freeze-dried (FD) and stored at -18°C till further use, as reported in earlier research publication (Alkndari et al 2019).…”
Section: Drying Of Amla Fruit Pulpmentioning
confidence: 99%